Aromaterapi Sebagai Terapi Nonfarmakologis Terhadap Mual dan Muntah pada Kehamilan: Literatur Review - Nurul Wahidah; Ulfa Nadia Nurul Firdaus; Siti Fatimah; Aryl Alfath Muhamad Iqbal; Dhiny Isma (Universitas Pahlawan Tuanku Tambusai, 2026)
Nausea and vomiting are common complaints during pregnancy that can disrupt the comfort and quality of life of pregnant women, so safe and effective non-pharmacological therapies such as aromatherapy are needed. Aromatherapy is a non-pharmacological complementary therapy that has been proven to provide a relaxing effect, reduce stress levels, and stimulate the limbic system that plays a role in regulating emotions and physiological responses of the body. This study aims to identify aromatherapy in reducing nausea and vomiting during pregnancy. The method used in this literature review uses the PICO Technique including: Population: pregnant women; Intervention: aromatherapy; Comparison: standard therapy or no aromatherapy given; Outcome: reduction in nausea and vomiting. The database used is Evidence Based Practice (EBP) from the Google Scholar, Science Direct and PubMed databases. The results of the study show that there are 8 articles published between 2021–2025 that mention several types of aromatherapy that can be used as a basis for applying complementary therapy for nausea and vomiting in pregnant women. It was concluded that aromatherapy with Lemon, Citrus Aurantium, Lavender, Peppermint, Ginger and Lemongrass has been proven to be significantly able to reduce nausea and vomiting during pregnancy, is safe, easy to apply, and can be used as an alternative non-pharmacological complementary therapy in midwifery care for pregnant women.